Recombination of Globally Circulating Varicella-Zoster Virus - Norberg, Peter (J Virol, 2015)
Varicella-zoster virus (VZV) is a human herpesvirus, which during primary infection typically causes varicella (chicken pox) and establishes lifelong latency in sensory and autonomic ganglia. Later in life, the virus may reactivate to cause herpes zoster (HZ; also known as shingles). To prevent these diseases, a live-attenuated heterogeneous vaccine preparation, vOka, is used routinely in many countries worldwide. Recent studies of another alphaherpesvirus, infectious laryngotracheitis virus, demonstrate that live-attenuated vaccine strains can recombine in vivo, creating virulent progeny. These findings raised concerns about using attenuated herpesvirus vaccines under conditions that favor recombination. To investigate whether VZV may undergo recombination, which is a prerequisite for VZV vaccination to create such conditions, we here analyzed 115 complete VZV genomes. Our results demonstrate that recombination occurs frequently for VZV. It thus seems that VZV is fully capable of recombination if given the opportunity, which may have important implications for continued VZV vaccination. Although no interclade vaccine-wild-type recombinant strains were found, intraclade recombinants were frequently detected in clade 2, which harbors the vaccine strains, suggesting that the vaccine strains have already been involved in recombination events, either in vivo or in vitro during passages in cell culture. Finally, previous partial and complete genomic studies have described strains that do not cluster phylogenetically to any of the five established clades. The additional VZV strains sequenced here, in combination with those previously published, have enabled us to formally define a novel sixth VZV clade. IMPORTANCE Although genetic recombination has been demonstrated to frequently occur for other human alphaherpesviruses, herpes simplex viruses 1 and 2, only a few ancient and isolated recent recombination events have hitherto been demonstrated for VZV. In the present study, we demonstrate that VZV also frequently undergoes genetic recombination, including strains belonging to the clade containing the vOKA strain.